Analysis of Organic Matter in Sediments and Macrozoobenthos from Coastal Waters of Hurun Bay of Lampung - Siregar, Jumahat; Nedi, Syahril; Mulyadi, Aras (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted in July 2015 with the aim to observe the macrozoobenthospopulation and organic matter content in the sediment. The samples were collected from HurunBay in Lampung Province with using survey method. Samples were analyzed in the Laboratoryof Water Quality BBPPL Lampung and Chemistry Laboratory, Faculty of Fisheries and MarineSciences University of Riau. The study showed that the organic content in the sediment between22.88 - 54.91%, while the abundance of macrozoobenthos was between 20.29 - 66.67 ind / m2.Macrozoobenthos identified in Hurun Bay 8 species, 3 classes and 2 phylua. From the phylum ofMollusca there were Gastropod i.e. which had 5 species and from the classes of bivalves thestudy also found two species. From the phylum annelid there was one class, Polychaeta and onespecies, i.e. Nereis sp. The relationship between macrozoobenthos and organic content wasexpressed with the equation of Y = 9,411 + 0,6268X that the relationship of organic matter withmacrozoobenthos abundance was weak.Keywords: Lampung, sediment, organic, makrozoobenthos